UTILIZATION OF QRIS E-WALLET IN GENERATION Z: RISK AND SECURITY PERSPECTIVE - Icha Radisa; Citra Nur Diana; Dwi Mia Widyasari; Arinal Muna (Cirebon International Conference on Education and Economics Proceeding, 2024)
Technological advancements have revolutionized payment systems, notably through the adoption of the Quick Response Indonesian Standard (QRIS) in e-wallet platforms. this study investigates the impact of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Perceived Risk (PR) and Perceived Security (PS) on Generation Z’s intention to use QRIS e-wallets. The Technology Acceptance Model (TAM) serves as the theoretical framework, employing snowball sampling for data collection. the analysis is conducted using SmartPLS 4.0, yielding significant findings: PU and PS positively influence intention to use QRIS e-wallets for transactions, whereas PEOU and PR show no significant impact. these results suggest that ecnhancing user-friendly features and ensuring robust security measures could bolster QRIS e-wallet adoption rates among Generation Z. In its practical implications, financial institutions and platform providers are encouraged to improve security and minimize the risks posed by QRIS e-wallets. The liminations of research is that only focuses on one generation and not in general QRIS e-wallet users. In addition, this research contributes to evaluating the effectiveness and efficiency of a non-cash payment system that can provide benefits, convenience, minimize the risk and security of users, especially generation Z in the context of QRIS e-wallet.